Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = - ( 1+2+3 +....+ 202) = - 203. 101 = -20503
B= ( 1+2-3-4) + ( 5+6-7-8) +..........+( 97+98 -99-100) + ( 101+102)
= -4 + (-4) .........+ (-4) + 203
= -4 .25 + 203 = 103
B=22+42+...+1002
B= 2.2 + 4.4 + 6.6+...+ 100.100
B= 4 + 16 + 36 +....+ 10000
B= 1.4 + 4.4 + 4.9+ ....+ 4.2500
B= 4( 1+4+9+....+2500)
B:4 = 1+4+9+....+2500
B:4= 1+22+32+...+502
B:4= 1+ 2.2 + 3.3+....+50.50
B:4= 1+ 2(1+1) + 3(1+2)+..............+50(49+1)
B:4= 1+ 2.1 + 2.1 + 3.1 + 3.2 +....+ 50.49+50.1
B:4= 1+ 2.1+ 2 + 3 + 3.2 +.....+ 50.49 + 50
B:4= (1.2 + 2.3 + 3.4 + ....+ 49.50) + (1+2+3+....+50)
Đặt A= 1.2+2.3 + 3.4+ 4.5+...+ 49.50
3A = 3(1.2+2.3 + 3.4+ 4.5+...+ 49.50)
3A= 1.2.3 + 2.3.3 + 3.4.3+...+49.50.3
3A= 1.2.3 + 2.3(4-1) + 3.4( 5-2)+....+49.50(51-48)
3A= 1.2.3 + 2.3.4 - 1.2.3+ 3.4.5 - 2.3.4 +...+ 49.50.51 - 48.49.5A
3A= 49.50.51
3A= 124950
A= 124950:3
A=41650
Đặt C= 1+2+3+....+50
Tổng C có số số hạng là: (50-1):1+1=50 số
Tổng là: 50(50+1):2=1275
=> B:4= A+C
B:4= 41650+ 1275
B:4=42925
B= 42925.4
B= 171700
Vậy....
\(3\cdot\left(x-2\right)^2=2+25\)
\(\Leftrightarrow3\cdot\left(x-2\right)^2=27\)
\(\Leftrightarrow\left(x-2\right)^2=9\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=3\\x-2=-3\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=5\\x=-1\end{cases}}\)
A = 3-32+33-34+35-....-3100
3A = 32-33+34-35+36-.....-3101
4A = 3A + A = 3 - 3101
=> A = \(\frac{3-3^{101}}{4}\)